Environmental Justice Education in Nepal: Policies and Practices - Sharma, Sushil; Paudel, Mohan; Singh, Ashik; Milligan, Lizzi; Singh, Ganesh Bahadur (Prithvi Academic Journal, 2024)
Environmental justice is fundamental to education and policy, ensuring clean environments and sustainable development. The curriculum and constitution of Nepal focus on this, addressing global gaps and encouraging comprehensive wellbeing measures for educational resilience. This paper analyzes how environmental justice is reflected through equitable treatment and meaningful participation of all people in the creation, implementation, and enforcement of environmental laws, regardless of their race, culture, education, and socioeconomic status. To analyze how environmental justice has been enforced in educational policies, interviews were conducted with five policymakers who have long experience in policymaking in the educational sector. The findings revealed that indigenous knowledge, cultural thought, and belief in environmental justice areas were considered major issues in education policies and practices. This study emphasizes the interconnectedness of local and global environmental issues and the need to bridge the gap. The integration of environmental justice in the national curriculum framework highlights the role of local expertise, indigenous knowledge, and practical application. The study recognizes the significance of environmental consciousness, sustainable development, and equal access to education. This study acknowledges constitutional provisions in Nepal supporting environmentally friendly and sustainable development. It emphasizes the importance of environmental education, equitable treatment, and compensation for environmental injustices to safeguard the environment for future generations.